Intra‐population variation in the natal origins and wing morphology of overwintering western monarch butterflies Danaus plexippus. Issue 10 (10th December 2015) - Yang, Louie H.; Ostrovsky, Dmitry; Rogers, Matthew C.; Welker, Jeffery M.
Abstract : Understanding the natal origins of migratory animals is critical for understanding their population dynamics and conservation. However, quantitative estimates of population recruitment from different natal habitats can be difficult to assess for many species, especially those with large geographic ranges. These limitations hinder the evaluation of alternative hypotheses about the key movements and ecological interactions of migratory species. Here, we quantitatively investigated intra‐population variation in the natal origins of western North American monarch butterflies Danaus plexippus using spatial analyses of stable isotope ratios and correlations with wing morphology. A map of hydrogen isotope values in western monarch butterfly wings (δ 2 Hm ) was estimated using a transfer function that relates the δ 2 Hm values of monarch butterfly wing keratin to a long‐term dataset of precipitation isotope (δ 2 Hp ) values across the western United States. Isotopic analyses of 114 monarch butterfly wings collected at four California overwintering locations indicated substantial individual variation in natal origins, with most recruitment coming from broad regions along the Pacific coast, the southwestern US and the northern intermountain region. These observed patterns may partially resolve and reconcile several past hypotheses about the natal origins of western monarch butterflies, while also raising new questions. More negative δ 2 Hm values (associated with longer migratory distance) were significantly correlated with larger forewing sizes, consistent with expectations based on the aerodynamic and energetic costs of long‐distance migration, while analyses of wing shape suggest potential differences in the movement behaviors and constraints observed in the western range, compared with previous observations in eastern North America. Taken together, the results of this study indicate substantial individual variation in the natal origins of overwintering western monarch butterflies, suggesting both local and long‐distance movement to overwintering sites.